Organization of palliative and hospice care worldwide and in Ukraine : Handbook for independent work in preparation for practical classes for 6th-year students of speciality “Medicine” - Rastvorov, O. A.; Yasinskyi, R. M.; Mironchuk, Y. V.; Растворов, Олександр Анатолійович; Ясінський, Роман Миколайович; Мирончук, Юлія Валеріївна (Запорізький державний медико-фармацевтичний університет, 2023)
Since the beginning of the 1970s, in most developed countries and at the beginning of the 21st century in Ukraine as well, the issue of developing palliative and hospice care has become one of the pressing medical, social, and humanitarian problems of society. The development of the economy, advances in medicine, the humanization of society and many other factors have led to an increase in the average life expectancy, resulting in a larger population of individuals with incurable diseases, elderly and aging individuals, children with limited life expectancy, and disabled individuals.